Mechanisms of Allostery and Membrane Attachment in Ras GTPases: Implications for Anti-Cancer Drug Discovery - Gorfe, A. A. (Current Medicinal Chemistry, 2010)
Ras GTPases are membrane-anchored molecular switches that mediate signaling pathways controlling a variety of cellular processes, including cell division and development. Despite their prominent role in many forms of cancer, little is known about the structure of the membrane bound protein or the mechanism and thermodynamics of membrane insertion. The modulation of membrane binding by the catalytic domain is another area of on-going scrutiny. Recent computational and experimental efforts that have begun to shed some light on these issues are the subject of this review. The bulk of the available structural and thermodynamic information on membrane-bound Ras has been obtained by studying peptides derived from the membrane-anchoring regions of N-ras and H-ras proteins. However, those results have been complemented by data, though limited, on the membrane binding of the full-length Ras as well as by predictions about putative communication routes between the GTP-hydrolyzing catalytic domain and the membrane-interacting C-terminus. A tentative mechanistic picture of Ras signaling that is emerging from these studies will be discussed in connection with allostery and implication for the design of selective anti-cancer drugs.
Keywords: dynamics